The blood antioxidant defence capacity during intermittent hypoxic training in elite swimmers - Poprzęcki, S; Czuba, M; Zając, A; Karpiński, J; Wilk, R; Bril, G; Maszczyk, A; Toborek, M (Biology of Sport, 2016)
he main objective of this study was to examine the chronic effect of simulated intermittent normobaric hypoxia on blood antioxidant defence capacity in swimmers. The study included 14 male and 14 female competitive swimmers performing part of land training under simulated intermittent normobaric hypoxia (O2 = 15.5%) or in normoxia. Land interval training took place twice per week, with a total of 8 training units during the study, performed with individualized intensity. The activities of blood antioxidant enzymes did not change significantly during the first and last training unit in the hypoxic and normoxic group. However, when comparing individual variables a significant effect of exercise was observed on GPx an CAT activities, whereas training units significantly differentiated GPx and GR activities. The oxygen conditions and gender had a significant influence on CAT activity. The total antioxidant capacity was not significantly affected. Only in male swimmers from the hypoxic group did the training significantly increase resting levels of MDA. In conclusion, training in normobaric hypoxia was not an adequate stimulus for the excessive response of the antioxidant defence system, despite increased oxidative stress in these conditions.